The Effect of Breastfeeding Counseling on Exclusive Breastfeeding Practices Among Postpartum Mothers: A Quasi-Experimental Study - Masliha; Weni Apriyani (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Exclusive breastfeeding remains a global health priority, yet its practice is often suboptimal, particularly in developing countries. Despite widespread awareness campaigns, many mothers discontinue exclusive breastfeeding before six months, leading to increased risks of infant morbidity and mortality. Maternity nurses play a vital role in bridging the gap by providing education, counseling, and support from the antenatal to the postpartum period. This study aimed to analyze the effect of breastfeeding counseling on exclusive breastfeeding practices among postpartum mothers. Methods: A quasi-experimental study with a pre–post design was conducted in the working area of Jatisawit Community Health Center, Jatibarang District. A total of 70 postpartum mothers (35 in the intervention group and 35 in the control group) were recruited through purposive sampling. The intervention group received structured breastfeeding counseling, while the control group received routine maternal care. Data were collected using a validated questionnaire and observation checklist, then analyzed using descriptive and inferential statistics. Ethical approval was obtained from the relevant ethics committee. Results: The findings revealed significant differences between the two groups. Mothers in the intervention group demonstrated higher adherence to exclusive breastfeeding practices compared to the control group. Counseling improved mothers’ knowledge, attitudes, and confidence, which translated into consistent exclusive breastfeeding behavior. Discussion and Suggestion: This study supports the evidence that breastfeeding counseling is an effective nursing intervention to promote exclusive breastfeeding. It highlights the essential role of maternity nurses as educators and supporters. Strengthening structured, continuous, and community-based counseling is recommended to improve breastfeeding practices. Future research should explore long-term outcomes and incorporate socio-cultural determinants to design more contextually relevant interventions.